Probiotics' effects on gut microbiota in jaundiced neonates: a randomized controlled trial protocol - Jiayi, Chen; Jinying, Wei; Yanhan, Yuan; Tianyu, Liu; Juanjuan, Chen; Feng, Zhang; Xiaohui, Fang; Jinping, Zhang (Frontiers in Pediatrics, 2024)
Impact:1.we aim to examine the effects of AB-GG, Bb-12 and M-16V and their combination on the intestinal microbiota, metabolomics and phototherapy-related side effects in neonates with jaundice.2.Prior research has employed these probiotics in treating various pediatric conditions, such as inflammatory bowel disease, milk protein allergy, and eczema.3.However, there are limited reports on their use in treating neonatal jaundice, and no systematic clinical research program has been established.4.This study aims to investigate the application of these three probiotics in neonatal jaundice treatment. 5.It may develop a clinical research protocol that may serve as a reference for other neonatal pediatricians.